2020
DOI: 10.2147/cmar.s246000
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy and Safety of Anlotinib in Advanced Non-Small Cell Lung Cancer: A Real-World Study</p>

Abstract: Purpose: The ALTER0303 trial showed that anlotinib, a novel antiangiogenic tyrosine kinase inhibitor, administered as third-line or further treatment prolonged progression-free survival (PFS) and overall survival (OS) in patients with advanced non-small cell lung cancer (NSCLC). This retrospective study investigated the efficacy and safety of anlotinib in real-world settings. Patients and Methods: Medical records of patients with advanced NSCLC receiving anlotinib as third-line or further treatment were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 32 publications
15
25
0
Order By: Relevance
“…In the present study, univariate analysis showed significantly longer PFS in patients without EGFR mutation than in patients with the mutation. However, consistent with previous studies ( 12 , 13 , 30 ), cox regression analysis showed both EGFR status and previous EGFR target therapy were not independent risk factors for PFS in patients receiving anlotinib. EGFR-TKIs are standard first-line treatment for NSCLC patients with EGFR mutations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the present study, univariate analysis showed significantly longer PFS in patients without EGFR mutation than in patients with the mutation. However, consistent with previous studies ( 12 , 13 , 30 ), cox regression analysis showed both EGFR status and previous EGFR target therapy were not independent risk factors for PFS in patients receiving anlotinib. EGFR-TKIs are standard first-line treatment for NSCLC patients with EGFR mutations.…”
Section: Discussionsupporting
confidence: 87%
“…Zhang et al. also reported brain metastases had no influence on PFS of NSCLC patients treated with anlotinib alone ( 13 ). However, in line with wu et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the PFS bene t of the combination was observed in the subgroups with or without previous antiangiogenic therapy, although the upper limit of the 95% CI exceeded 1. These ndings are consistent with those in earlier studies, which showed that previous antiangiogenic therapy had no in uence on PFS and OS of ≥ third-line anlotinib treatment in aNSCLC (Han et al 2018;Shao et al 2019;Zhang et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of adverse events recorded in both groups was low and similar to those reported in the literature [25,[40][41][42][43][44][45][46]. In this study, the proportion of patients rechecking ECG, thyroid function and urine routine was small.…”
Section: Discussionsupporting
confidence: 86%